Molecular Identification of Elvers (Anguilla spp.) from River Estuaries in Central Java, Indonesia Using DNA Barcoding Based on mtDNA CO1 Sequences - Iffan Nadhif Falah; Ratih Ida Adharini; Susana Endah Ratnawati (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research